Nanocellulose from Agricultural Waste for Neonatal and Biomedical Implant Applications - Singh Chouhan, Chetan; Dagur, Hitin; Kant Rahi, Ravi (Journal of Neonatal Surgery, 2025)
Nanocellulose, a nanoscale form of cellulose derived from plant biomass, has emerged as a promising sustainable material owing to its exceptional properties such as high mechanical strength, large surface area, biocompatibility, biodegradability, and surface chemistry. This review explores the extraction of nanocellulose from various agricultural residues including wheat straw, rice husk, sugarcane bagasse, corn stalks, and coconut husk using eco-friendly methods such as acid hydrolysis, enzymatic treatment, and mechanical disintegration. Emphasis is placed on optimizing extraction processes to yield biomedical-grade nanocellulose while minimizing environmental impact. The application of nanocellulose in biomedical implants, particularly for neonatal use, is discussed with a focus on its roles in tissue engineering scaffolds, wound healing matrices, and drug delivery systems. Its structural similarity to natural extracellular matrices, along with non-toxicity and minimal immunogenicity, makes nanocellulose a highly favourable material for sensitive clinical applications. Additionally, functionalization of nanocellulose surfaces enables antimicrobial, anti-inflammatory, and regenerative enhancements tailored to neonatal care. This review highlights the dual benefits of agricultural waste valorisation and the development of advanced green biomaterials, positioning nanocellulose as a next-generation component in biomedical implants while addressing sustainability and health care innovation.